The effect of placenta previa on fetal weight and feto-maternal blood flow: a prospective cohort study - Ali, Mohammed K.; Mahfouz, Islam S.; Abbas, Ahmed M.; Sayed, Ezzat H. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: The current study aims to evaluate the effect of placenta previa on the fetal weight and to explore its effect on the uterine and umbilical arteries blood flow. Methods: The current study was a prospective cohort study conducted at Assiut Women’s Health Hospital, Egypt from 1st of October 2016 to 30th of September 2017 including placenta previa and non-placenta previa women. They were followed up by two-dimensional ultrasound and Doppler blood flow in the uterine and umbilical arteries. The main study outcome was the number of low birth weight (LBW) babies delivered at or beyond 37 weeks and blood flow changes in uterine and umbilical arteries. Results: Two hundred twelve women were divided into two groups; group I included 106 placenta previa women (PP group) and 106 non-placenta previa women (NPP group). The number of LBW babies were comparable in both groups without statistically significant difference (P value= 0.555). Neither; uterine artery nor umbilical artery blood flow had any significant differences between the groups. Preterm delivery was significantly higher in the PP group (p value=0.000). Conclusions: Although there is no agreement, in the literature, on the association between placenta previa and LBW, authors suggest that placenta previa is not a reason for LBW babies. In addition, placenta previa shows no effect on uterine artery or umbilical artery blood flow.